Territoriia . Territoriia . Territory . Территория - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. A program about the civil war in Georgia and subsequent economic and social problems. Featured in the program: Shevardnadze, Eduard Amvrosievich (President of Georgia) Contributors: Vladina, Kira (Anchor) Передача о гражданской войне в Грузии и связанных с ней экономических и социальных проблемах. В программе участвуют: Шеварднадзе, Эдуард Амвросиевич (Президент Грузии) Создатели: Владина, Кира (Ведущий/Ведущая)